Thin, soft, garment‐integrated triboelectric nanogenerators for energy harvesting and human machine interfaces - Liu, Yiming; Yiu, Chunki; Jia, Huiling; Wong, Tszhung; Yao, Kuanming; Huang, Ya; Zhou, Jingkun; Huang, Xingcan; Zhao, Ling; Li, Dengfeng; Wu, Mengge; Gao, Zhan; et al. (EcoMat (Beijing, China), 2021)
The applications of triboelectric nanogenerators (TENGs) in wearable electronics for energy harvesting and motion sensing have raised extensive attentions, since TENGs enable to convert body motions induced mechanical energy into electrical signals. The development of thin, soft, and garment‐integrated TENGs would be an important solution for the power management in wearable electronics as well as self‐powered sensors. Here, we report materials, device designs, processing routes for garment‐integrated TENGs (G‐TENGs) and demonstrations of the G‐TENGs in wearable energy harvesting and human‐machine interfaces. The G‐TENGs adopt a simple layout with two soft silicone layers and one graphene‐coated fabric layer, exhibiting great flexibility, air‐permeability, and robust durability. Furthermore, the G‐TENGs present outstanding electrical characteristics with open‐circuit voltage and short‐current outputs as great as 213.75 V and 3.11 μA, under a constant frequency and stress of 3 Hz and 5.6 kPa, respectively. The excellent mechanical properties of the G‐TENGs allow them tolerating toward over 1000 cycles of bending, stretching and twisting, and maintaining unchanged electrical outputs after these deformations. The stable electrical outputs and the excellent mechanical performance of the G‐TENGs provide a high potential in self‐powered sensors, energy harvesting, human‐machine interfaces and many others. Thin, flexible, garment‐based triboelectric nanogenerators were developed for energy harvesting and motion sensing. By optimizing the mechanical properties of the device, the air‐permeable TENGs have exhibited excellent electrical performance. The simple fabrication process offers a new strategy of high‐throughput, large‐area, and low‐cost self‐powered electronics for energy harvesting and human machine interfaces.